Intermolecular Metal-Catalyzed Reductive Coupling of Dienes, Allenes and Enynes with Carbonyl Compounds and Imines - Holmes, Michael (Chem Rev, 2018)
Metal-catalyzed reductive coupling has emerged as an alternative to the use of stoichiometric organometallic reagents in an increasingly diverse range of carbonyl and imine additions. In this monograph, the use of diene, allene and enyne pronucleophiles in intermolecular carbonyl and imine reductive couplings are surveyed along with related hydrogen auto-transfer processes.